DEPRESSION AND PAIN COMMORBIDITY: A JOURNEY THROUGH THE LIVES OF FAMED MUSICIANS - JOSE, DIVYA ANNE; PRADEEP, UTHARA; Meera B (International Journal of Psychosocial Rehabilitation, 2020)
Depression is the most co-morbid psychiatric disorder in people who die by suicide. It is as ‘living in an endless black hole’ or having an emotion of impending doom. The feeling of hopelessness, helplessness and worthlessness is unrelenting and intense. To identify and intensify the threat of this growing disorder, the paper aims on a systematic analysis of depression, which is prevalent among English singers who committed and attempted suicide, and those who suffered from depression and self-abuse. From the way we move to the way we laugh, depression changes everything about life. It even changes the way you speak and the expression of your writing. Sometimes the language of depression is much powerful than the effect of others.The paper concentrates on the depressive behavioural traits of famed singers and the innumerable complexities in their lyrics and their suicides. Many of these musicians killed themselves after suffering from depression for years. To create awareness about the hazard of this threat in our present scenario, we concentrate on the recently demised rock band singers Chester Bennington and Kurt Cobain. To strengthen the literary aspects and research theories, the paper is built upon the information collected from diary entries, journals, interviews, and biographies of the demised singers and their beloved ones. The greatest achievements of these individuals, their lyrics, are analyzed in depth to interpret the emotions and state of mind.